Penerapan keselamatan dan kesehatan kerja sebagai upaya pencegahan kecelakaan kerja di PT. Perusahaan Gas Negara (Persero) Tbk tahun 2023 - Sitepu, Zefanya Nesha Endhaiya; Tarigan, Lina (Talenta Publisher, 2024)
Occupational Safety and Health is one way to protect workers from work accidents and dangerous risks. K3 is carried out by the company based on applicable company laws and regulations. The implementation of Occupational Safety and Health at the Pasar IX Gas Station functions to protect workers from the risk of occupational hazards at the gas station. The aim of this research is to analyze the implementation of occupational safety and health as an effort to prevent work accidents at PT. Perusahaan Gas Negara (Persero) Tbk 2023. Descriptive research method with a qualitative approach which aims to analyze the implementation of occupational safety and health at the Pasar IX Gas Station – PT. Perusahaan Gas Negara Tbk. Informants were taken using a purposive sampling technique, totaling 7 people, namely 1 HSSE person, 3 fire fighter team members, and 3 first aid team members. The selected informants are considered to be able to provide information regarding the implementation of occupational safety and health which includes K3 policies, K3 communications, K3 inspections and K3 evaluations. The research results show that the implementation of K3 at PT. Perusahaan Gas Negara Tbk has been running well and is in accordance with applicable regulations. The K3 policy is established and signed by the main director. K3 communication is carried out by HSSE to promote and inform workers to implement occupational safety and health. K3 inspections are carried out to check the condition of all equipment, work environment and worker actions. K3 evaluation is carried out by HSSE and the K3 Audit Institute to assess the extent of K3 implementation. As a research suggestion, the Pasar IX gas station operator collaborates with the Fire Department and hospitals in holding K3 training to increase awareness and knowledge of occupational safety and health among station workers.